Tiered teacher competency qualification standards as CPD guide VHS teachers - Sri Waluyanti; Herminarto Sofyan (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
The purpose of research is to produce a tiered teacher qualification standards of competence and qualification assessment levels rise as a guide ongoing professional development of teachers of VHS.Type mix of research methods, approaches Research and Development of Richey and Klein (2009, p.8) are limited to 2 stages of development and product validation. Internal validation by expert judgment Delphi Technique 2 rounds and FGD. External validation of the test product on teachers vocational competency skills Techniques Audio Video in Yogyakarta. Retrieving data using questionnaires. Test the validity of the instrument using factor analysis with SPSS version 20, the validity of 77.781% in the high category. Cronbach alpha reliability coefficient of 0.896 in the category of very reliable. Data were analyzed using the Rank-Order of Difference Scores.Stakeholders assess differences in the demands of professional competence and work area clear hierarchy between the teacher. Standard assessment level rise is able to describe the complexity of teaching. Effectiveness qualification standards can be improved mainly through the standard explanation tiered competence and qualifications, assessment of real professional attributes inherent in the everyday lives of teachers.